Mushroom Consumption Behavior and Influencing Factors in a Sample of the Portuguese Population - Boin, Elisa; Nunes, João (Journal of international food & agribusiness marketing, 2018)
Although mushroom consumption is a trend due to new eating habits, little investigation on the influencing factors is available. Therefore, a study was carried out with 925 subjects from Portugal: socio-demographic and mushroom consumption data were collected, namely overall frequency of consumption, consumption by type (canned, fresh, dried or frozen) and by species (five cultivated and four wild mushrooms). Results were analyzed by descriptive analysis and ordered logistic regression. In general, mushroom consumption was high (81.9%), where canned mushrooms were more consumed than fresh, and dried/frozen were scarcely consumed. Subjects with higher education consumed mushrooms more frequently, as women were more likely to consume mushrooms and age was positively associated with frequency of consumption. Household size, educational level, and gender were the factors that influenced most consumption. This study presents a background on mushroom consumption and socio-demographic influencing factors, as a pillar for further behavioral studies on this subject.